The Role of Mexico's Plural in Latin American Literary and Political Culture - King, J. author. aut Link
IX, 242 p.
Keywords: In this book, the Mexican magazine Plural (1971-1976) provides a privileged vantage point from which to assess the developments that transformed Mexican and Latin American literary and political culture in the 1970s.